ANATOMY AND PHARMACOGNOSY OF TAVERNIERA CUNEIFOLIA ROOT (ROTH) ARN., A POSSIBLE SUBSTITUTE OF GLYCYRRHIZA GLABRA L. - P. S. MANGALORKAR; B. R. PATEL; P. S. NAGAR (International Journal of Pharma and Bio Sciences, 2013)
Taverniera cuneifolia is an important traditional medicinal plant of India belonging to the family of Fabaceae. The roots of Taverniera cuneifolia is a potential substitute of Glycyrrhiza glabra (Licorice). In order to differentiate G. glabra from T. cuneifolia, macroscopic as well as microscopic studies of T.cunefolia were done. The present investigation deals with pharmacognostic characters, which includes anatomy, powder studies and histochemical test.